Geospace variability during the 2008–2009 Whole Heliosphere Intervals. Issue 5 (5th May 2014) - Lean, J. L.; McDonald, S. E.; Huba, J. D.; Emmert, J. T.; Drob, D. P.; Siefring, C. L.
Abstract We simulate the ionosphere and thermosphere throughout the extended solar minimum epoch from 2008 to 2009 using geospace models, systematically validating the models with databases of observed geospace composition. We isolate and quantify observed changes of as much as 4 total electron content unit (TECU) (1 TECU = 1016 elections m−2) (~36%) in global (60°S−60°N) ionospheric total electron density and as much as 19 × 10−12 kg m−3 (~75%) in global thermospheric mass density at 250 km associated with fluctuating solar EUV radiation and geomagnetic activity during this nominally "quiet" period. Corresponding modeled responses to both solar EUV radiation and geomagnetic activity are about a factor of 2 smaller than is observed. We identify, as well, semiannual and annual oscillations that produce geospace variability comparable to that produced by external solar and geomagnetic influences, and which cause distinct differences among the three individual Whole Heliosphere Intervals. From the first Whole Heliosphere Interval (March–April 2008) to the third Whole Heliosphere Interval (June–July 2009) total electron content (60°S−60°N) decreased 3.6 TECU (~32%) and mass density at 250 km decreased 9 × 10−12 kg m−3 (~34%) due to these oscillations. Reliable attribution of the geospace base state during the 2008–2009 solar minimum epoch and geospace comparisons among the Whole Heliosphere Intervals thus requires that the semiannual and annual oscillations be properly distinguished in addition to the concurrent solar and heliospheric effects which have been the primary goal of the majority of Whole Heliosphere Interval (WHI) characterizations.